Peran Website Hasil Program Pengabdian Mahasiswa dalam Meningkatkan Akses Informasi UMKM Batik Butupaku - Aulia Syafitri; Trisna Septiani; Hadizatul Habibny; Sularno .; Novadilastri . (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The development of information technology encourages Micro, Small, and Medium Enterprises (MSMEs) to utilize digital media as a means of information and promotion. This study analyzes the role of student-generated Project Based Learning (PBL) websites as digital information and promotion media for Batik Butupaku MSME in Padang Panjang City. The research method uses descriptive qualitative with data collection techniques including observation, interviews, and documentation. The results show that before the website existed, information dissemination about Batik Butupaku MSME was limited to social media and direct communication, resulting in unintegrated information. Website implementation provides convenience for consumers to obtain information about business profile, products, services, contact, and ordering processes more systematically. The website plays a role in enhancing digital promotion by increasing MSME visibility through search engines, expanding market reach from various regions, strengthening business image and professionalism, supporting product branding as Padang Panjang specialty batik, and supporting MSME digital transformation. Thus, student-generated Project Based Learning websites can serve as effective information and promotion media for Batik Butupaku MSME.